Estudo da codifica??o de rede e an?lise do seu desempenho com fonte de tr?fego HTTP - Silva, Daniel Carli Colares e (2017)
The volume of data traffic on the Internet grows exponentially. The web traffic is estimated to be over 70% of traffic generated on the Internet. Currently, several technologies are being investigated for a better utilization of bandwidth for the transmission of applications, and network coding technique is one. This work presents some studies on network coding techniques and their benefits, as well as a performance analysis with traffic source HTTP using the methods store-and-forward. This performance analysis is done at a topology bottleneck node in a butterfly net considering two ways to download, HTTP/1.0-busrt transfer mode, and HTTP/1.1-persistent transfer mode. In the scenarios investigated both theoretically and via simulation, the network coding makes better use of the transmission rate of a linkage to compared store-and-forward method traditional.